Dari Sekadau ke Sabu Raijua: Menakar Jejak Bawaslu dalam Dinamika Persidangan di Mahkamah Konstitusi - Rima Yuwana Yustikaningrum; Mohammad Mahrus Ali (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
The Election Supervisory Body (Bawaslu) in the hearing of 2020 Regional Head Election Dispute played an essential role as a supervisor and its statements in the field became one of the keys for the Constitutional Court of Justice to obtain balanced, neutral or impartial information. This article focuses on the role and track record of Bawaslu as the supervisor of the Regional Head Elections in the vortex of controversy. Disputes over the results of the regional head elections in the Constitutional Court. In PHPKada, these include North Morowali Regency, Boven Digoel Regency, Sekadau Regency, Pesisir Selatan Regency, and Sabu Raijua Regency where Bawaslu always presents information on the results of supervision in every trial at the Constitutional Court. The facts of the trial that were revealed cannot be separated from the judicial strengthening of Bawaslu's role and the Panel of Judges can elaborate deeper into the results of field supervision. The process of proof in the trial of the Constitutional Court by examining the evidence, witness statements are also equipped with the submission of the results of the report by the party giving the information, namely Bawaslu. The addition of this authority makes Bawaslu no longer just a recommending institution, but also decide the election case.